1998
DOI: 10.1088/0953-8984/10/9/011
|View full text |Cite
|
Sign up to set email alerts
|

Electrical studies on trap levels present in n- and p-type spray pyrolysed CdS thin films

Abstract: Trap levels in n- and p-type spray pyrolysed CdS thin films were analysed using thermally stimulated current (TSC) and dark-conductivity measurements. TSC measurements of the n-type sample revealed the presence of only one peak under light excitation for a short period due to mobility of sulphur vacancies, but longer excitation could give evidence of one more level which was due to a complex of cadmium and sulphur vacancies. TSC spectra of the p-type sample indicated the presence of two levels of comparable cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The level is observed in sample CS5 Zhao et al [8] detected the level at 0.47 eV using photoluminescence measurements and attributed it to a native defect (cadmium interstitial?). Also Zeenath et al [4] and Vigil et al [6] reported on a level at 0.41 eV detected using TSC measurements and attributed it to a complex native defect (cadmium and sulfur vacancies complexes?) 6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The level is observed in sample CS5 Zhao et al [8] detected the level at 0.47 eV using photoluminescence measurements and attributed it to a native defect (cadmium interstitial?). Also Zeenath et al [4] and Vigil et al [6] reported on a level at 0.41 eV detected using TSC measurements and attributed it to a complex native defect (cadmium and sulfur vacancies complexes?) 6.…”
Section: Resultsmentioning
confidence: 99%
“…L9 (0.72 eV): The level is observed in sample CS5. Zeenath et al [4] observed a level at 0.75 eV using TSC measurements which they attributed to copper impurities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation